(untitled) (Sains Humanika, 2010)
This research discusses Data Envelopment Analysis (DEA) model to evaluate the relative performance of public university libraries in Malaysia. DEA model is a suitable method to evaluate relative performances of a set of homogeneous decision–making units (DMUs). The basic concept of DEA is to identify the efficient decision–making units among all DMUs. This efficient DMU is called a Pareto optimal unit and is considered as the standard for comparison of all inefficient DMUs. In this study, the dual analysis will be carried out for the inefficient libraries in order to interpret the inefficiency in terms of the inputs and outputs. The outcomes of this dual analysis will give the management the improvements that need be done to the inefficient libraries, in terms of reducing the inputs and increasing the outputs. Suitable inputs and outputs for evaluating the performance of DMUs are determined using the isotonicity test. The study is carried out on 14 public university libraries and the results showed that 8 libraries are efficient while 6 are inefficient.